Role of entrepreneurship education in developing students' entrepreneurial mindset - Miftahul Nur Utami Amalia Sholiha; Susantiningrum Susantinigrum; Subroto Rapih (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2025)
Abstrak: Penelitian ini bertujuan untuk mengetahui peran pendidikan membangun mindset berwirausaha siswa kelas XII Manajemen Perkantoran SMK Negeri 6 Surakarta. Penelitian kuantitatif korelasional dengan populasi siswa kelas XII Manajemen Perkantoran SMK Negeri 6 Surakarta tahuni pelajaran 2023/2024 dengan jumlah sampel 85 responden. Penelitian ini diambil menggunakan teknik cluster random sampling. Metode pengumpulan data menggunakan kuesioner atau angket. Teknik analisis data menggunakan teknik analisis regresi linier berganda dengan bantuan program kerja IBM SPSS 25. Dari hasil penelitian dapat disimpulkan bahwa terdapat pengaruh positif dan signifikan pendidikan kewirausahaan terhadap mindset berwirausaha (nilai thitung 10,453 >ttabel 1,98932), Kontribusi pendidikan kewirausahaan sebesar 56.8%, sedangkan 43,2% dipengaruhi oleh faktor lain yang tidak termasuk dalam penelitian. Kata kunci: kewirausahaan; mindset; pendidikanAbstract: This study aims to investigate the role of entrepreneurship education in developing entrepreneurial mindset among Grade XII Office Management students at SMK Negeri 6 Surakarta. This correlational quantitative research involved a population of Grade XII Office Management students at SMK Negeri 6 Surakarta for the 2023/2024 academic year, with a sample of 85 respondents selected using cluster random sampling technique. Data collection employed questionnaire methods, and data analysis utilized multiple linear regression techniques with IBM SPSS 25. Results demonstrate a positive and significant effect of entrepreneurship education on entrepreneurial mindset (t-calculated 10.453 > t-table 1.98932, p < 0.001). The contribution of entrepreneurship education accounts for 56.8% of variance in entrepreneurial mindset, while 43.2% is influenced by other factors not included in this study. These findings suggest that well-structured entrepreneurship education programs can effectively foster entrepreneurial thinking patterns among vocational students, contributing to the development of future entrepreneurs who can create employment opportunities and reduce unemployment rates. Keywords: education; entrepreneurship; mindset